Conceptual substantiation of the directions of improvement of project management of the development of physical culture and educational space in the university - Ya.A. Goncharuk; S.V. Goncharuk; A.V. Voronkov; T.I. Shkolina (Theory and Practice of Physical Culture, 2023)
Objective of the study was to determine the level of involvement of actors in the physical culture and educational space of a modern university. Methods and structure of the study. The analytical basis of this scientific work is the sociological study "Diagnostics of the management system of the sports and educational space of universities" (2018-2021), which was conducted in the Belgorod, Kursk and Lipetsk regions. The study sample consisted of students (n=1000), university professors and researchers (n=300). Along with the survey, focus group interviews were conducted with teachers and researchers of universities (n=12). Results and conclusions. All actors of the physical culture and educational space of a modern university are characterized by a fairly high level of awareness of the goals of the sports and educational space, which can provide the necessary communication between subjects and form a unified approach to achieve the goals. For teachers and employees, as well as for administrators, it is typical only for occasional involvement in the processes taking place in it; for the majority, the norm is the actual detachment from it when declaring the significance of this activity. Not all teachers and researchers believe that their professional experience and potential in the conditions of the sports and educational space of the university is fully realized. It is concluded that at the moment the level of involvement of students, teachers and researchers cannot be fully recognized as optimal and requires further transformation through the management technologies of the physical culture and educational space of a modern university.